Fairness Principles in Islamic Social Funds: An Analysis of Zakat and Wakaf Management in Indonesia: Prinsip Keadilan dalam Dana Sosial Islam: Analisis Pengelolaan Zakat dan Wakaf di Indonesia - Susila, Sugeng; Alhadiansyah; Djunastuti, Erni; Marnita; Prihatin, Angga (Rechtsidee, 2023)
This study explores the implementation of the fairness principle in the management of Islamic social funds through zakat and wakaf in Indonesia, guided by existing legal frameworks and theoretical sources. Employing a legal approach, it critically examines and evaluates various laws related to the management of Islamic social funds in Indonesia. The research method utilized is a normative legal study focusing on theoretical examination and analysis of relevant legal documents and regulations. The findings reveal that the management of zakat and wakaf in Indonesia reflects the Fairness Principle, aiming to ensure just and equitable distribution and utilization of Islamic social funds. Such just management has significantly positive impacts on economic empowerment and societal welfare in Indonesia, enhancing education access, social infrastructure strengthening, productive business development, and empowerment of vulnerable groups, thus reducing poverty and social inequality. Collaboration between Islamic social fund institutions, government, and society is crucial to ensuring effective and sustainable utilization in enhancing Indonesia's overall economic welfare and societal well-being.Highlights: Implementation of the fairness principle in managing Islamic social funds (zakat and wakaf) ensures equitable distribution and utilization. Management significantly impacts economic empowerment and societal welfare in Indonesia. Strong collaboration between institutions, government, and society is key to effective and sustainable utilization of zakat and wakaf. Keywords: Zakat, Wakaf, Fairness Principle, Economic Empowerment, Welfare Enhancement